Perbedaan Posisi Miring dan Setengah Duduk pada Ibu Bersalin terhadap Kelancaran Persalinan Kala II di RB Puskesmas Kecamatan Matraman Tahun 2021 - Noviyani, Ernita Prima; Ruliyah, Siti; Thompson, Maria (Lembaga Publikasi Ilmiah Nusantara, 2023)
Maternal mortality is death that occurs during pregnancy, childbirth and the postpartum period due to certain causes. Indonesia is in the third highest rank for Maternal Mortality Rate (MMR) in ASEAN countries. The first rank is Laos with 470/100,000 live births, while the lowest is Singapore with 3/100,000 live births. This study is an experimental study of static group comparison (static group comparison), namely observing the quasi-experimental group (delivery position tilted to the left) and the experimental group (sitting position of labor). It was found that there was a difference in the average value of the second stage of labor between the half-sitting and left-sided labor positions. The second stage in the standing position group was 26.87 minutes, while the second stage in the left tilted position group was 23.60 minutes, with a difference in the average value of 3.27 minutes. The half-sitting position has advantages, namely the birth canal groove that needs to be achieved to be able to get out shorter and the earth's gravity to lower the fetus into the pelvic cavity. While the tilted position to the left has the advantage of providing a relaxed feeling for the mother to get the baby out. However, from the results of hypothesis testing using an independent T test, it was found that the p value: 0.670 > alpha (0.05) which means that there is no significant difference between the exercise position and tilted to the left on monitor II.